Elevating English Writing Skills Via Social Networking Sites (SNS): Focusing on Indonesian Undergraduate Students Perceptions - Izzah, Nurul; Febriyanti, Rina Husnaini (JEdu: Journal of English Education, 2023)
Since writing in English appears to be an issue for EFL learners, particularly in academic settings for undergraduate students, there is a need to identify some ways or methods of teaching that may assist students in improving their writing ability, such as implementing different platforms like Social Networking Sites (SNS) for teaching and learning English writing skills in the hopes that it will help students enhance their proficiency. This research aims to ascertain how SNS are used to improve writing skills in English by examining Indonesian undergraduates' perspectives and their preferences for English writing practice on their SNSs. This study employed a qualitative approach as the research design. The participants of this study were 42 undergraduate students majoring in English education at a private university in Jakarta, Indonesia. The research instruments employed a questionnaire and an interview. The results revealed that the utilization of SNS as a tool for English writing learning is perceived as helpful and beneficial for the development of undergraduate students' English writing skills.